Social construction of the arts volunteer : a case in the Singapore Mandarin theatre. - Kao, Jamie Peixin. (2011)
Volunteering is a complex social phenomenon that has been widely studied by scholars across disciplines. Many have contributed to the profile of a volunteer by defining his or her motivations, scope of work and context of volunteering. In this study, however, I am interested in comparing the official discourse of the ‘arts volunteer’ with the self-representations given by arts volunteers in Singapore. My findings suggest youth art volunteers do not consider themselves altruistic contrary to official discourse, instead, they volunteer out of a sense of social obligation and finally, out of their self-interest in volunteering, they seek to experience (time after time) the ‘magic of theatre’. I argue that disjuncture between official discourse and self-representation of the ‘arts volunteer’ construct impacts negatively on volunteering policy effectiveness. I will illustrate this with a case in Singapore’s Mandarin theatre in which I conclude with a policy recommendations to boost the local arts and cultural scene.